2010
DOI: 10.1073/pnas.1001707107
|View full text |Cite
|
Sign up to set email alerts
|

A distinct DGAT with sn -3 acetyltransferase activity that synthesizes unusual, reduced-viscosity oils in Euonymus and transgenic seeds

Abstract: Endosperm and embryo tissues from the seeds of Euonymus alatus (Burning Bush) accumulate high levels of 3-acetyl-1,2-diacyl-snglycerols (acTAGs) as their major storage lipids. In contrast, the aril tissue surrounding the seed produces long-chain triacylglycerols (lcTAGs) typical of most other organisms. The presence of the sn-3 acetyl group imparts acTAGs with different physical and chemical properties, such as a 30% reduction in viscosity, compared to lcTAGs. Comparative transcriptome analysis of developing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
161
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(168 citation statements)
references
References 40 publications
8
161
0
Order By: Relevance
“…This distinct structure results in the reduced viscosity and the significantly lower energy density of acTAGs compared with lcTAGs (Durrett et al, 2010). Trace amounts of acTAGs have been described in a broad range of organisms, including the antlers of Japanese deer (Cervus nippon) (Yang et al, 2004), the udders of domestic cows (Bos primigenius) (Limb et al, 1999) and the seeds of the burning bush plant (Euonymus alatus) (Durrett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This distinct structure results in the reduced viscosity and the significantly lower energy density of acTAGs compared with lcTAGs (Durrett et al, 2010). Trace amounts of acTAGs have been described in a broad range of organisms, including the antlers of Japanese deer (Cervus nippon) (Yang et al, 2004), the udders of domestic cows (Bos primigenius) (Limb et al, 1999) and the seeds of the burning bush plant (Euonymus alatus) (Durrett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This distinct structure results in the reduced viscosity and the significantly lower energy density of acTAGs compared with lcTAGs (Durrett et al, 2010). Trace amounts of acTAGs have been described in a broad range of organisms, including the antlers of Japanese deer (Cervus nippon) (Yang et al, 2004), the udders of domestic cows (Bos primigenius) (Limb et al, 1999) and the seeds of the burning bush plant (Euonymus alatus) (Durrett et al, 2010). acTAGs constitute a very small proportion of the total lipid pool in the two mammal species investigated [<0.1% by mass Limb et al, 1999;Yang et al, 2004)], but predominate (92% by moles) in E. alatus seed oils (Durrett et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DGAT genes have been isolated from many organisms. At least two forms of DGATs are present in mammals (Cases et al, 1998;Cases et al, 2001) and plants Shockey et al, 2006) with additional forms reported in burning bush (Euonymus alatus) (Durrett et al, 2010), peanut (Saha et al, 2006), and Arabidopsis (Rani et al, 2010). Plants and animals deficient in DGATs accumulate less TAG (Smith et al, 2000;Stone et al, 2004;Zou et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Animals with reduced DGAT activity are resistant to diet-induced obesity Smith et al, 2000) and lack milk production (Smith et al, 2000). Over-expression of DGAT enzymes increases TAG content in plants (Andrianov et al, 2010;Bouvier-Nave et al, 2000;Burgal et al, 2008;Durrett et al, 2010;Jako et al, 2001;Lardizabal et al, 2008;Xu et al, 2008), animals (Kamisaka et al, 2010;Liu et al, 2009;Liu et al, 2007;Roorda et al, 2005), and yeast (Kamisaka et al, 2007). DGATs have nonredundant functions in TAG biosynthesis in species such as mice (Stone et al, 2004) and tung tree (Vernicia fordii) (Shockey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%